One of God's "Bad Moods": Kafka's Social Diagnosis and its Multiple Interpretations - Yvanka Raynova (Labyrinth: An International Journal for Philosophy, Value Theory and Sociocultural Hermeneutics)
In this editorial for the special issue on Franz Kafka, Yvanka B. Raynova examines Kafka's relationship to Nietzsche as well as the very different and often contradictory interpretations of Kafka's work by philosophers and literary critics. She argues that although Kafka's novels cannot be directly "translated into a philosophical, theological, sociological, or psychoanalytical discourse" (Jürgen Born), they should not be interpreted and evaluated solely from a literary perspective, as they raise institutional questions that have led to socio-critical and political associations that are just as urgent for us today. In this context, she refers to the controversies surrounding Kafka's work in Eastern Europe during the Cold War, to his current socio-political reception in art, and to the Kafkaesque in the contemporary world.